QoS Analysis for 5G Networks - Lekhashree K S; Ms Gayetri; Arathi R Shankar (Journal of Electronic Design Engineering, 2018)
Fifth generation (5G) is the wireless network technologies, which is designed to provide efficient quality of service in mind. The performance seen by the users of the network will primarily depend on QoS elements. Thus, by managing QoS – Bit rate, Throughput, Transmission delay, packet loss, and Jitter parameters can improve to manage the network resource efficiently. The 5G system is a combination of many different modulation techniques; this is done to ensure improvement in performance and further to result in greater-efficiency in the output. The author has made an attempt to analyze different modulation techniques with the coding scheme and compare the QoS performances between them. The performances have been analyzed for two schemes QPSK and QAM using Viterbi coding scheme. Thus for both the modulation technique with Viterbi coding scheme excellent performances were recorded, thereby providing an optimum solution to maintain QoS.